PENGARUH PERTUMBUHAN PENJUALAN DAN STRUKTUR MODAL TERHADAP PERTUMBUHAN LABA DENGAN FIRM SIZE SEBAGAI VARIABEL KONTROL PADA SUBSEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BEI PERIODE 2020 – 2024 - Faridah Rahmawati; Cynthia Eka Violita (P3M Politeknik Negeri Banjarmasin, 2026)
This study investigates influence sales growth and capital structure on profit growth by considering firm size as a control variable in food and beverage companies listed on Indonesia Stock Exchange (IDX) over 2020–2024 period.Observation period was restricted 2024 because audited financial statements for 2025 fiscal year were not yet fully available for all sampled companies at time data were collected. Consequently, 2020–2024 period was selected to ensure consistency and reliability empirical analysis. The research adopts a quantitative approach using an associative research design, with sample determined through purposive sampling. The empirical findings reveal that sales growth has a positive and statistically significant influence on profit growth. In contrast, capital structure and firm size do not exhibit statistically significant partial effect on profit growth. However, simultaneous analysis confirms that these variables collectively have a significant influence on profit growth. The Adjusted R-Squared value 14.69% indicates model explains 14.69% variation in profit growth, while remaining 85.31% attributable other factors beyond scope proposed model. The main contribution this study is incorporation firm size as a control variable, allowing for a more comprehensive assessment relationship between sales growth, capital structure, and profit growth. The findings are expected contribute to developmen empirical research in financial management and provide useful insights for corporate managers and investors in designing strategies improve financial performance and support investment decision-making